Cosmetic Packaging Quality Analysis Using the Six Sigma and House of Quality Methods at PT XYZ - Roland Y.H. Silitonga; Marla Setiawati; Christabel Jovanka (Journal of Novel Engineering Science and Technology, 2026)
Product quality is a critical factor in the success of manufacturing industries, particularly in the cosmetic packaging sector, where packaging serves both protective and marketing functions. PT XYZ experienced a defect rate of 4.09% in cosmetic packaging products, resulting in increased production costs and reduced customer satisfaction. This study aims to reduce product defects by applying the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology integrated with Failure Mode and Effects Analysis (FMEA) and the House of Quality (HoQ). DMAIC was employed to identify defect sources, measure process performance, analyze root causes, implement improvements, and establish process control. FMEA was used to evaluate potential failure modes and prioritize corrective actions based on Risk Priority Numbers, while HoQ translated improvement priorities into practical technical actions. Data were collected through direct observation and interviews with relevant personnel at PT XYZ. The implementation of the proposed improvements reduced overall defects by 2,321.43 defects per million opportunities (DPMO), equivalent to 2.32%, and increased the process sigma level by 0.21. Specifically, the “Dirty Glass/Grepes” defect decreased by 11,616.07 DPMO (1.16%) with a sigma improvement of 0.58, whereas the “Scratch” defect declined by 5,660.71 DPMO (0.57%) with a sigma improvement of 0.25. Root cause analysis revealed that Dirty Glass/Grepes defects were primarily associated with human and method factors, while Scratch defects were related to human, equipment, and method factors. Seven improvement alternatives were identified, with two successfully implemented: adding a blower stage during final assembly and inspecting the cover pull-force testing instrument.